Streamlining ε-PL Production: Recent Trends in Fermentation and Downstream Processing - Saglam, Bahar; Kalkan, Melis; Ustun-Aytekin, Ozlem; Aytekin, Ali Ozhan (WILEY, 2026)
The derivatives of poly-lysines have a wide range of applications such as food additives, drug carriers, nanoparticles, and hydrogels. The epsilon-poly-L-lysine (epsilon-PL) is one of the important derivatives of poly-lysine. Due to its biodegradability, water solubility, and non-toxicity; epsilon-PL is the most preferred one in these areas. Streptomycetaceae strains produce epsilon-PL and the main industrial producer microorganism is Streptomyces albulus. epsilon-PL can be produced by chemical or biological processes; however, fermentation processes are preferable for its yield. To sustain cost-effective production, different studies were performed in the approach of strain isolation and improvement, medium optimization, operation modes, and innovative separation and purification methods. This review discusses recent advancements in purification methods, highlighting techniques that enhance purity and scalability for industrial applications and provides valuable insights to optimize epsilon-PL production and tailor its properties for diverse applications.
Keywords: epsilon-poly-l-lysine; fed-batch fermentation; Streptomyces albulus; purification; POLY-L-LYSINE; MIXED CARBON SOURCE; STREPTOMYCES-ALBULUS; POLYLYSINE PRODUCTION; MEDICAL APPLICATIONS; EFFICIENT PRODUCTION; BIOSYNTHESIS; GLUCOSE; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology